The novel engulfment receptor Six-microns-under acts upstream of Draper in the glial phagocytosis of apoptotic neurons - Kurant, Estee (2008)
The removal of apoptotic cells by phagocytic neighbors is essential for metazoan development but remains poorly characterized. Here we report the discovery of a novel Drosophila phagocytosis receptor, Six-microns-under (SIMU), which is expressed in highly phagocytic cell types during development and required for efficient apoptotic cell clearance by glia in the nervous system and by macrophages elsewhere. SIMU is part of a conserved family of proteins that includes CED-1 and Draper (DRPR). Phenotypic analysis reveals that simu acts upstream of drpr in the same pathway and affects the recognition and engulfment of apoptotic cells, while drpr affects their subsequent degradation. SIMU strongly binds to apoptotic cells, presumably through its EMILIN-like domain, but requires no membrane anchoring, suggesting that it can function as a bridging molecule. Our study introduces an important new factor in tissue-resident apoptotic clearance and underscores the prominent role of glia as ‘semi-professional’ phagocytes in the nervous system.